2007
DOI: 10.1002/fld.1636
|View full text |Cite
|
Sign up to set email alerts
|

Correlated observation errors in data assimilation

Abstract: Data assimilation provides techniques for combining observations and prior model forecasts to create initial conditions for numerical weather prediction (NWP). The relative weighting assigned to each observation in the analysis is determined by its associated error. Remote sensing data usually has correlated errors, but the correlations are typically ignored in NWP. Here we describe three approaches to the treatment of observation error correlations. For an idealised data set, the information content under eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
132
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(141 citation statements)
references
References 5 publications
9
132
0
Order By: Relevance
“…The results also showed that the analysis became less accurate in certain combinations of the error correlation and the angle in the observation operator. The results agree very well in the conceptual model based on the Shannon information content (Stewart et al 2008;MKL13).…”
Section: Summary and Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The results also showed that the analysis became less accurate in certain combinations of the error correlation and the angle in the observation operator. The results agree very well in the conceptual model based on the Shannon information content (Stewart et al 2008;MKL13).…”
Section: Summary and Discussionsupporting
confidence: 77%
“…MKL13 suggested that for analysis accuracy in data assimilation the available information in the observations be essential rather than the amount of information based on the Shannon information content (Stewart et al 2008). Recent studies suggested that some observations have correlated errors, but the observation error covariance matrix R is assumed to be diagonal in the operational numerical weather prediction systems.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, attempts have been made to quantify error correlation structure for a few different observation types such as Atmospheric Motion Vectors (Bormann et al, 2003) and satellite radiances (Sherlock et al, 2003;Stewart et al, 2009;Stewart, 2010;Stewart et al, 2012). Using diagnosed correlations such as these in an operational assimilation system is far from straightforward: early attempts by the UK Met Office using IASI and AIRS data have resulted in conditioning problems with the 4D-Var minimisation (Weston, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Under these assumptions, increasing the observation density beyond some threshold value has been shown to yield little or no improvement in analysis accuracy (Liu and Rabier, 2003;Berger and Forsythe, 2004;Dando et al, 2007). Stewart et al (2008) and Stewart (2010) showed that the observation information content in the analysis is severely degraded under the incorrect assumption of independent observation errors. Such studies, combined with examples demonstrating that ignoring correlation structure hinders the use of satellite data [e.g.…”
Section: Introductionmentioning
confidence: 99%